PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA MATIC PADA DRIVER OJEK ONLINE DI KOTA SURABAYA - Isnawati, Linda; Rafida, Veni (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
This research aims to analyze the influence of Brand Image and Product Quality on the purchasing decisions of Honda Matic motorcycles among Online motorcycle taxi Drivers in Surabaya. The research employs a quantitative approach. The sample consists of 350 Online motorcycle taxi Drivers who use Honda Matic motorcycles in the city of Surabaya. Data collection is done through a questionnaire, which is validated and tested for reliability using SPSS 26. The data analysis techniques include classical assumption tests, linear regression, t-tests, f-tests and the coefficient of determination (R-Square). The results of this study indicate that both Brand Image and Product Quality partially influence the purchasing decisions of Honda Matic motorcycles. Simultaneously, these two variables significantly impact the purchasing decisions of Honda Matic motorcycles.